The Discovery And Evaluation Of The Ellendale And Argyle Lamproite Diamond Deposits, Kimberley Region, Western Australia (cc90e79b-6e14-466b-9f1c-4f617be935ae) - W. J. Atkinson (Society for Mining, Metallurgy & Exploration, 1984)
Since the inception of the Ashton (formerly Kalumburu) Joint Venture in 1972 the parties have expended 524 million in exploration for diamonds in the Kimberley region. This has resulted in the discovery of the currently subeconomic Ellendale deposits in 1976/77 and the economic Argyle - Smoke Creek Deposits in 1979/80. In addition to Argyle and Ellendale some 90 kimberlitic and lamproitic bodies have been discovered grouped broadly into three provinces, on the west, east and north margins of the Kimberley block. These bodies range in size from dyke-like features less than one metre in width to pipes with a surface area of 128ha. The bodies with larger surface area are volcanic crater deposits, infilled with air-fall and water deposited tuffs and epiclastic sediments.